A new species of Pseudoparaclius Grichanov (Diptera: Dolichopodidae) from Udzungwa Mountains National Park, Tanzania, and a key to Afrotropical species - Kaae, Mathias Emil; Grichanov, Igor; Pape, Thomas (Zootaxa, 2015)
Pseudoparaclius udzungwa sp. nov. is described from Udzungwa Mountains National Park, Tanzania, and a key to all known Afrotropical species of Pseudoparaclius Grichanov is provided. Pseudoparaclius udzungwa is morphologically very similar to P. sanjensis (Grichanov) but has a modified male fore tarsus with laterally compressed tarsomeres 4–5, an epandrium with slightly shorter marginal teeth distiventrally, a blunt-tipped sclerotized part of the hypandrium, and an almost straight phallus. Males of P. udzungwa and P. sanjensis share a characteristic, oval, cup-shaped cercus not seen in any other known species of Pseudoparaclius.